2016
DOI: 10.1016/j.trgeo.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The influence of tree root water uptake on the long term hydrology of a clay fill railway embankment

Abstract: This paper uses a numerical model to investigate the influence of tree root water uptake and tree removal on pore water pressures and the vertical movement of a clay fill railway embankment. Simulated results of soil wetting and drying are compared with field measurements from an instrumented railway embankment before and after tree removal. A parametric study compares the influence of vegetation on the seasonal movement of the embankment slope. The simulations and field measurements show that while trees caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Figure 17 also shows the Feddes function based on the parameters commonly adopted in geotechnical applications (diamonds) (u w3 = À100 kPa, u w4 = À1500 kPa (Nyambayo & Potts, 2010;Briggs et al, 2016)). The discrepancy with the experimental data is remarkable.…”
Section: The Use Of Hct To Inform the Transpiration Reduction Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 17 also shows the Feddes function based on the parameters commonly adopted in geotechnical applications (diamonds) (u w3 = À100 kPa, u w4 = À1500 kPa (Nyambayo & Potts, 2010;Briggs et al, 2016)). The discrepancy with the experimental data is remarkable.…”
Section: The Use Of Hct To Inform the Transpiration Reduction Functionmentioning
confidence: 99%
“…The approach proposed by Feddes et al (1978) to model the reduction factor is widely used in geotechnical applications (Hemmati et al, 2010;Nyambayo & Potts, 2010;Greco et al, 2013;Briggs et al, 2016;Tsiampousi et al, 2017;Pagano et al, 2019;Zhu & Zhang, 2019). This approach is convenient because it only requires information about the pore-water pressure in the root zone without the need to address the complex interaction between the soil, the plant, and the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Such modelling has been successfully adopted for investigating different issues: e.g. embankment stability analysis (Gitirana Jr., 2005;Briggs et al, 2016), soil-structure interaction (Al Qadad et al, 2012) and generic soil-water budget (Cui et al, 2005).…”
Section: Predictive Modelsmentioning
confidence: 99%
“…Baum et al, 2008;Pagano et al, 2010;Formetta et al, 2016). In other applications evaporation is taken into account by following approaches with different degree of complexity (Casadei et al, 2003;Rosso et al, 2006;Šimunek et al, 2006;Ebel et al, 2010;Formetta et al, 2014;Capparelli and Versace, 2011;Arnone et al, 2011;Endrizzi et al, 2014). Complete approaches, modelling internal and boundary evaporation through hydrothermal approaches, were taken into account in studies referred to slopes in finegrained soils differing substantially from those involved in the case at hand (Cui et al, 2005;An et al, 2017;Song et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The Hawkwell site was back analysed by Briggs et al (2016), using the commercial finite element software Vadose/W to try to match the observed changes in soil water content and pore water pressure. Using a set of carefully considered climate, soil water retention, permeability and plant parameters (rooting depth, and root water abstraction with depth), it was found that the model could replicate fairly well the field observed changes.…”
Section: Modelling Vegetation Climate and Slope Failuresmentioning
confidence: 99%